Evaluation of Arbuscular Mycorrhizal Fungi Capacity to Alleviate Abiotic Stress of Olive (Olea europaea L.) Plants at Different Transplant Conditions - María Josefina Bompadre; Mariana Pérgola; Laura Fernández Bidondo; Roxana Paula Colombo; Vanesa Analía Silvani; Alejandro Guillermo Pardo; Juan Antonio Ocampo; Alicia Margarita Godeas (The Scientific World Journal)
The capacity of roots to sense soil physicochemical parameters plays an essential role in maintaining plant nutritional and developmental functions under abiotic stress. These conditions generate reactive oxygen species (ROS) in plant tissues causing oxidation of proteins and lipids among others. Some plants have developed adaptive mechanisms to counteract such adverse conditions such as symbiotic association with arbuscular mycorrhizal fungi (AMF). AMF enhance plant growth and improve transplant survival by protecting host plants against environmental stresses. The aim of this study was to evaluate the alleviation of transplanting stress by two strains of Rhizophagus irregularis (GC2 and GA5) in olive. Our results show that olive plants have an additional energetic expense in growth due to an adaptative response to the growing stage and to the mycorrhizal colonization at the first transplant. However, at the second transplant the coinoculation improves olive plant growth and protects against oxidative stress followed by the GA5-inoculation. In conclusion, a combination of two AMF strains at the beginning of olive propagation produces vigorous plants successfully protected in field cultivation even with an additional cost at the beginning of growth.